Environmental, Social and Governance (ESG) Implementation at A Malaysian Public University: An Exploratory Case Study - Abu Samah, Arif Safiuddin; Musli Mohammad, (Research Progress in Mechanical and Manufacturing Engineering, 2025)
The principles of Environmental, Social, and Governance (ESG) have become increasingly essential to higher education, particularly in Malaysian public universities. These organizations are essential to the advancement of research, shaping future leaders, and the progress of sustainable development. However, constraints include limited budget, fragmented strategy, limited stakeholder engagement, and a lack of execution frameworks that occasionally make implementing ESG initiatives in public universities challenging. The objectives of this study are to identify critical factors for ESG implementation, evaluate the readiness of ESG initiatives implementation, and suggest an ESG implementation framework. The research methodology is an exploratory case study conducted at Universiti Tun Hussein Onn Malaysia (UTHM). The data collection method involves the use of interviews, observations, and ESG readiness assessment surveys. The results reveal the critical factors that ESG initiatives implement are leadership commitments, clear ESG policies, funding, performance measurements, talent development and knowledge, and stakeholder engagement. The general understanding of ESG has scored a median readiness of 1 or low readiness. While, ESG criteria have a median readiness score of 2, or moderate readiness, according to the analysis, which shows that UTHM has made significant progress but still needs to improve considerably. Examples of ESG initiatives implementation such as solar panel installation for environmental practice, corporate social responsibility (CSR) for social practice, and energy efficiency management policy for governance practice. Additionally, the ESG implementation framework has been proposed for UTHM involving six critical factors.